Sytuacja dziecka niepełnosprawnego w szkole = The situation of disabled child in school - Kunysz-Rozborska, Magdalena (Journal of Education, Health and Sport, 2016)
Kunysz-Rozborska Magdalena. Sytuacja dziecka niepełnosprawnego w szkole = The situation of disabled child in school. Journal of Education, Health and Sport. 2016;6(7):103-112. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57170 http://ojs.ukw.edu.pl/index.php/johs/article/view/3660 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. SYTUACJA DZIECKA NIEPEŁNOSPRAWNEGO W SZKOLE THE SITUATION OF DISABLED CHILD IN SCHOOL Magdalena Kunysz-Rozborska Wydział Wychowania Fizycznego, Uniwersytet Rzeszowski Mgr Magdalena Kunysz-Rozborska Wydział Wychowania Fizycznego, Uniwersytet Rzeszowski Streszczenie Artykuł ma na celu ukazanie wybranych aspektów sytuacji, w jakiej znajduje się dziecko niepełnosprawne umysłowo lub fizycznie w szkole pośród swoich w pełni sprawnych rówieśników. Stopień upośledzenia może przyjąć formy utrudniania, ograniczania i uniemożliwiania orientacji w otoczeniu, zdobywaniu wiedzy, czynnościach życia codziennego, poruszania się w przestrzeni, pracy zawodowej, integracji społecznej, a także niezależności ekonomicznej. Efektywność procesu kształcenia ucznia z niepełnosprawnością w szkole ogólnodostępnej zależy od bardzo wielu czynników. Jednym z głównych warunków jest jakość usługi edukacyjnej oferowanej uczniowi przez placówkę. Rzeczywistość pokazuje, jak duże trudności mają nauczyciele pracujący w szkołach integracyjnych w konstruowaniu indywidualnych programów nauczania dla konkretnych uczniów niepełnosprawnych i dostosowywaniu wymagań edukacyjnych do indywidualnych możliwości każdego z nich. Słowa kluczowe: uczeń niepełnosprawny, niepełnosprawność, zdrowie, aktywność ruchowa, upośledzenie. Summary The main aim of the article is to show some aspects of the situation in which the child is mentally or physically handicapped at school among their non-disabled peers. The degree of an impairment may take the form of hindering, reducing and preventing orientation in the environment, the acquisition of knowledge, activities of daily life, moving in space, work, social integration, and economic independence. The effectiveness of the learning process student with a disability in a mainstream school depends on many factors. One of the main conditions is the quality of educational services offered to the student by the facility. Reality shows how much difficulties the teachers have working at integration schools and designing an individual curricula for specific students with disabilities and adapting the educational requirements to individual potential for each of them. Key words: student with a disability, disability, health, physical effort, handicap.